2009
DOI: 10.1002/ptr.2947
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effect of mistletoe (Viscum album L.) extract on Jurkat cells and its interaction with doxorubicin

Abstract: Mistletoe preparations are frequently used by cancer patients because of their ability to stimulate the immunity and to improve the quality of life. Moreover mistletoe and its active substances (especially lectins) possess cytotoxic effect on various cancer cell lines. However, only little is known about its interaction with anticancer drugs. Therefore the cytotoxic and apoptosis-inducing effects of aqueous mistletoe extract (VA) and its interaction with doxorubicin (DOXO) were investigated in Jurkat cells. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 21 publications
1
9
1
1
Order By: Relevance
“…A previous study indicated that lectins selectively bind to malignant cells because they only bind to specific carbohydrates by recognizing domains present in cell membranes that are differentially expressed in non-tumor cells (Sharon, 2007; Sabova et al, 2010; Koh et al, 2011; Nolte et al, 2012). The internalization of lectin improves its intracellular availability and activity (Lichtenstein and Rabinovich, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…A previous study indicated that lectins selectively bind to malignant cells because they only bind to specific carbohydrates by recognizing domains present in cell membranes that are differentially expressed in non-tumor cells (Sharon, 2007; Sabova et al, 2010; Koh et al, 2011; Nolte et al, 2012). The internalization of lectin improves its intracellular availability and activity (Lichtenstein and Rabinovich, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The proteasome inhibitor bortezomib enhanced the antiproliferative property of mistletoe lectin on human G631 melanoma cells [136]. Also, combination of doxorubicin and mistletoe extracts containing lectin caused cytotoxicity and induced DNA fragmentation to human leukemia Jurkat cells [137]. The use of mistletoe extracts in clinical trials has shown promising results.…”
Section: Plant Lectinsmentioning
confidence: 98%
“…Iscador, the aqueous preparation of V. album L. is regarded a potent CAM. Sabova et al (2010) investigated the cytotoxic and apoptosis-inducing effects of aqueous mistletoe extract alone or in combination with doxorubicin on Jurkat cells. Dose-dependent DNA fragmentation was induced in Jurkat cells individually as well as synergistically.…”
Section: Synergistic Effectsmentioning
confidence: 99%